2021
DOI: 10.1037/per0000442
|View full text |Cite
|
Sign up to set email alerts
|

“I will love you (me) forever”—A longitudinal study of narcissism and emotional adjustment during the transition to motherhood.

Abstract: The aim of this study is to examine the differential implications of grandiose and vulnerable narcissism for women’s adjustment during the transition to motherhood. A total of 385 Israeli women participated in the study during their pregnancy (Time 1) and 2 months postpartum (Time 2). Participants filled out a battery of questionnaires assessing their levels of narcissism (Time 1), the body experience during pregnancy (Time 1) and motherhood (Time 2), their attachment to the fetus (Time 1) and to the baby (Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…suggest that during their first pregnancy, women report feeling less control and ownership over their bodies, that their bodies are stared at, touched and evaluated more, but also that they feel more attractiveness, femininity, pride, competence and self-confidence. In contrast to earlier studies (Mooney et al, 2023;Talmon et al, 2021;Talmon & Ginzburg, 2018), here, we adapted the Body Experiences scale to include a non-pregnant cohort, so this result confirms that these experiences related to the body are significantly different in pregnancy compared to women in the general population.…”
Section: Discussionsupporting
confidence: 52%
“…suggest that during their first pregnancy, women report feeling less control and ownership over their bodies, that their bodies are stared at, touched and evaluated more, but also that they feel more attractiveness, femininity, pride, competence and self-confidence. In contrast to earlier studies (Mooney et al, 2023;Talmon et al, 2021;Talmon & Ginzburg, 2018), here, we adapted the Body Experiences scale to include a non-pregnant cohort, so this result confirms that these experiences related to the body are significantly different in pregnancy compared to women in the general population.…”
Section: Discussionsupporting
confidence: 52%
“…Current, albeit sparse, literature alludes to narcissistic individuals engaging in dysfunctional parenting styles. Studies have found that narcissistic parents may employ sub-optimal parenting strategies in terms of permissiveness and authoritarianism (Hart et al 2017), prefer partners who are over-controlling as parents (Lyons et al 2020) and struggle to adjust during the transition to parenthood (Talmon et al 2020). However, very little is known about the damage that narcissistic parents can cause to their children later in life.…”
Section: They Fill You With the Faults They Hadmentioning
confidence: 99%
“…To date, studies related to the transition to motherhood have mainly focused on the psychological dimensions of pregnancy and giving birth [14,15]. Additionally, studies have dealt with attachment and bonding with children rather than the mother as the focal point [16,17].…”
Section: Introductionmentioning
confidence: 99%